The roles of urban agriculture to household food security: a case study in Kirkos sub-city, Addis Ababa city, Ethiopia - Firew Dereje Alene; Merga Abdissa Aga (Frontiers in Sustainable Food Systems, 2025)
IntroductionThe main objective of the study was to explore the contribution of urban agriculture (UA) to the household food security of urban farmers in Addis Ababa, using Kirkos Subcity as a case study.MethodsBoth quantitative and qualitative research approaches were employed to ascertain and describe the characteristics of variables of interest. The data collection involved surveys and interviews with urban farmers.ResultsThe study revealed that 48.2% of respondents were food secure, while 23.1% and 28.7% were mildly or moderately food insecure, respectively. Additionally, 33.8% of respondents believed that urban agriculture helped them meet their daily food needs, while the remaining respondents felt it was insufficient. Approximately 47.2% of respondents reported that UA helped them meet their food requirements year-round, whereas 22.6% said it was unable to cover their year-round needs. Most respondents indicated that their income increased due to engaging in urban agriculture. Furthermore, 72.3% of respondents had access to land resources for urban agriculture, while 27.7% did not have access to land. The ordinal logistic regression model indicated that age, family size, formal education, household head, monthly income, marital status, educational level, main income source, farming experience, land access, and market access were statistically significant predictors of household food security.DiscussionThe prevalence of food insecurity among urban households engaged in agriculture highlights the need for additional support and increased intensity of various types of urban agriculture. Policymakers should consider integrating urban agriculture into urban planning strategies to enhance food security and resilience in urban areas.